Stress-induced alterations in 5-HT1A receptor transcriptional modulators NUDR and Freud-1 - Szewczyk, Bernadeta; Kotarska, Katarzyna; Daigle, Mireille; Misztak, Paulina; Sowa-Kucma, Magdalena; Rafalo, Anna; Curzytek, Katarzyna; Kubera, Marta; Basta-Kaim, Agnieszka; Nowak, Gabriel; Albert, Paul R (The international journal of neuropsychopharmacology, 2014)
The effect of stress on the mRNA and protein level of the 5-HT1A receptor and two of its key transcriptional modulators, NUDR and Freud-1, was examined in the prefrontal cortex (PFC) and hippocampus (Hp) using rodent models: olfactory bulbectomy (OB) and prenatal stress (PS) in male and female rats; chronic mild stress in male rats (CMS) and pregnancy stress. In PFC, CMS induced the most widespread changes, with significant reduction in both mRNA and protein levels of NUDR, 5-HT1A receptor and in Freud-1 mRNA; while in Hp 5-HT1A receptor and Freud-1 protein levels were also decreased. In male, but not female OB rats PFC Freud-1 and 5-HT1A receptor protein levels were reduced, while in Hp 5-HT1A receptor, Freud-1 and NUDR mRNA's but not protein were reduced. In PS rats PFC 5-HT1A receptor protein was reduced more in females than males; while in Hp Freud-1 protein was increased in females. In pregnancy stress, PFC NUDR, Freud-1 and 5-HT1A protein receptor levels were reduced, and in HP 5-HT1A receptor protein levels were also reduced; in HP only NUDR and Freud-1 mRNA levels were reduced. Overall, CMS and stress during pregnancy produced the most salient changes in 5-HT1A receptor and transcription factor expression, suggesting a primary role for altered transcription factor expression in chronic regulation of 5-HT1A receptor expression. By contrast, OB (in males) and PS (in females) produced gender-specific reductions in PFC 5-HT1A receptor protein levels, suggesting a role for post-transcriptional regulation. These and previous data suggest that chronic stress might be a key regulator of NUDR/Freud-1 gene expression.